Pathogenesis, prophylaxis and treatment of internal recurrences of inguinal hernia - Croci, Fabio; Pérez Penco, Ernesto; Rabellino, Joaquín; Tarabochia, Carlos (Cirugía del Uruguay, 1986)
Internal recidivation; of the inguinal herniorrhaphy represents about 1/3 of the total number of same. This variety is: a) comparatively small; b)· usually palnful; e) difficult to repair. They are not the dlrect of prior pathology but are due to technical defects in the internal angle management owing to technical triangle, the anatomic configuration of which presents numerous variations. The appearance of a primary hernia at that level.